2023
DOI: 10.1002/agj2.21236
|View full text |Cite
|
Sign up to set email alerts
|

Winter wheat grain yield stability under different tillage practices

Abstract: Grain yield stability is vital for achieving yield consistency across a broad range of environments. The significance of this is well documented in crop genetic studies and may equally be relevant for tillage practices used in croplands. The objective of this study was to evaluate long-term winter wheat (Triticum aestivum L.) grain yield stability under different tillage practices. The study was designed as a randomized complete block with three replications. The independent variable was tillage with three lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This is particularly true for NT and SM, which over time had more SOM than MP. One previous study conducted at the same site suggested that grain yield averaged 2.6 Mg·ha −1 and that a 26‐year average grain yield did not vary by tillage practices (Aula et al., 2023). Another study conducted near the same site showed that applying several rates of N ranging from 0 to 125 kg·ha −1 had no substantial effect on grain yield in some years and an average yield of 2.7 Mg·ha −1 appears not substantially higher than the 26‐year average above (Ghimire et al., 2021).…”
Section: Discussionmentioning
confidence: 94%
“…This is particularly true for NT and SM, which over time had more SOM than MP. One previous study conducted at the same site suggested that grain yield averaged 2.6 Mg·ha −1 and that a 26‐year average grain yield did not vary by tillage practices (Aula et al., 2023). Another study conducted near the same site showed that applying several rates of N ranging from 0 to 125 kg·ha −1 had no substantial effect on grain yield in some years and an average yield of 2.7 Mg·ha −1 appears not substantially higher than the 26‐year average above (Ghimire et al., 2021).…”
Section: Discussionmentioning
confidence: 94%